2023
DOI: 10.3390/ani13040556
|View full text |Cite
|
Sign up to set email alerts
|

Immunity in Sea Turtles: Review of a Host-Pathogen Arms Race Millions of Years in the Running

Abstract: The immune system of sea turtles is not completely understood. Sea turtles (as reptiles) bridge a unique evolutionary gap, being ectothermic vertebrates like fish and amphibians and amniotes like birds and mammals. Turtles are ectotherms; thus, their immune system is influenced by environmental conditions like temperature and season. We aim to review the turtle immune system and note what studies have investigated sea turtles and the effect of the environment on the immune response. Turtles rely heavily on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 240 publications
(392 reference statements)
0
3
0
Order By: Relevance
“…Antibiotic-resistant bacteria should be taken into particular account as a major health concern of sea turtles because antibiotic treatment of hospitalized turtles may be unsuccessful [ 102 , 110 , 114 , 116 , 130 , 158 ]. However, evolution and severity of the infections, also those caused by opportunistic pathogens, are strongly related to sea turtles’ immune system status; the immune function is sensitive to fluctuations in temperature and to pollutants in the environment; and rapid changes in the marine environment are considered responsible for higher vulnerability to infections and diseases [ 159 ].…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotic-resistant bacteria should be taken into particular account as a major health concern of sea turtles because antibiotic treatment of hospitalized turtles may be unsuccessful [ 102 , 110 , 114 , 116 , 130 , 158 ]. However, evolution and severity of the infections, also those caused by opportunistic pathogens, are strongly related to sea turtles’ immune system status; the immune function is sensitive to fluctuations in temperature and to pollutants in the environment; and rapid changes in the marine environment are considered responsible for higher vulnerability to infections and diseases [ 159 ].…”
Section: Discussionmentioning
confidence: 99%
“…But unlike Aves, Crocodylus porosus has both Myristoylation motif and TRAF6 binding motif in TRAM protein and conserved serine in pLxIS motif of TRIF. TRAM in Chelonia mydas also lacks the CD14 and has viral RNA sensing by TLR3 mediated signalling [32]. Also, like Crocodylus porosus, it has conserved motifs and key residues.…”
Section: Insights From Representative Organismsmentioning
confidence: 99%
“…was suggested to be a possible vector of ChHV5 transmitting between sea turtles (Greenblatt et al, 2004). Nowadays, several studies suggested that FP in sea turtles is mainly caused by the interaction of ChHV5 and environmental factors such as water quality and autoimmunity (Aguirre et al, 1995;Alfaro-Nunez et al, 2016;Bruno et al, 2021;James et al, 2021;Sposato et al, 2021;Nash & Ryan, 2023). Sea turtles with FP were shown to have immunosuppression and reduced activity of natural killer cells (Work et al, 2001;Li and Chang, 2020;Perrault et al, 2021).…”
Section: Introductionmentioning
confidence: 99%